Electrochemical carbon dioxide capture to close the carbon cycle. Issue 2 (12th January 2021) - Sharifian, R.; Wagterveld, R. M.; Digdaya, I. A.; Xiang, C.; Vermaas, D. A.
Abstract : An overview of the state-of-the-art for capturing CO2 via electrochemical routes. Abstract : Electrochemical CO2 capture technologies are gaining attention due to their flexibility, their ability to address decentralized emissions ( e.g., ocean and atmosphere) and their fit in an electrified industry. In the present work, recent progress made in electrochemical CO2 capture is reviewed. The majority of these methods rely on the concept of "pH-swing" and the effect it has on the CO2 hydration/dehydration equilibrium. Through a pH-swing, CO2 can be captured and recovered by shifting the pH of a working fluid between acidic and basic pH. Such swing can be applied electrochemically through electrolysis, bipolar membrane electrodialysis, reversible redox reactions and capacitive deionization. In this review, we summarize main parameters governing these electrochemical pH-swing processes and put the concept in the framework of available worldwide capture technologies. We analyse the energy efficiency and consumption of such systems, and provide recommendations for further improvements. Although electrochemical CO2 capture technologies are rather costly compared to the amine based capture, they can be particularly interesting if more affordable renewable electricity and materials ( e.g., electrode and membranes) become widely available. Furthermore, electrochemical methods have the ability to (directly) convert the captured CO2 to value added chemicals and fuels, and hence prepare for a fully electrified circular carbon economy.